Comprehensive description of a skeleton of Endothiodon Bathystoma (Anomodontia, Therapsida), a dicynodont from the Late Permian of the Karoo Basin of South Africa - Maharaj, Iyra Esmen Maeve (Department of Biological Sciences, 2019)
The dicynodonts are an extinct group of herbivorous non-mammalian synapsids that were fairly abundant in Gondwanan deposits of the middle Permian to the Early Triassic periods. The extinct genus Endothiodon was first described by Sir Richard Owen in 1876, and is well known from the late Permian deposits of the Karoo Basin of South Africa. It is characterized by rows of internal teeth on the premaxilla and dentary arranged in replacement waves called Zahnreihen; longitudinal ridges running from the premaxilla to the pineal crest; and a prominent pineal boss with a pineal foramen. Endothiodon is well-represented by cranial and postcranial material in the Karoo vertebrate collections at various museums in South Africa. The repeated taxonomic revision of this genus over the years has led to much confusion about what constitutes the type species, E. bathystoma. Recently, an almost complete skeleton of Endothiodon (SAM-PK-K011271) was recovered from the uppermost Pristerognathus Assemblage Zone of the Karoo Supergroup. The fossil comprises the skull and most of its postcranial elements preserved in articulation. The current study provides a comprehensive description of the anatomy of this specimen, which permitted its identification as E. bathystoma. Furthermore, by comparison with other South African Endothiodon specimens this study determined that this specimen is the second largest E. bathystoma specimen known to date. The well-preserved skull and postcranial skeleton of SAM-PK-K011271 makes it an ideal reference specimen for E. bathystoma and has permitted a good assessment of its overall anatomy. The findings of this study provide a perfect stepping-stone for future studies to further address E. bathystoma’s skeletal reconstruction and biomechanical functions, as well as other aspects of the palaeobiology of this animal.